Про акцентуаційний спосіб словотворення - Винницький, В.М. (Мовознавство, 2007)
У статті з’ясовано функційне навантаження наголосу при розмежуванні й аналізі двох типів омографів. Цю проблему розглянуто із словотвірного погляду, наголос визначається як словотворчий засіб, за допомогою якого утворюються нові слова різних морфологічних класів. Поставлено питання про існування акцентуаційного способу словотворення, визначено його статус. The article focuses on the functional role of the word-stress in the process of delimitation and analysis of the two types of homographs. This problem has been discussed from the word-formative point of view and the word-stress has been defined as a word-formative device which helps to form new words of different morphological classes. The question of the existence of the accentual word-formation has been raised, its status defined.